2021
DOI: 10.1016/j.celrep.2021.109118
|View full text |Cite
|
Sign up to set email alerts
|

Resident memory T cells in tumor-distant tissues fortify against metastasis formation

Abstract: Christian et al. show that tumor-derived resident memory T cells (T RM s) are developed in tumors, as well as in distant and tumor-free mucosal tissues. Distant T RM s are developed from T Eff/EM precursors that are trapped within the tumor. The release of such retention can be achieved by CXCR6/CXCL16 blockade, which leads to prevention against metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 98 publications
0
18
0
Order By: Relevance
“…An ambivalent role of CXCR6 + T cells in tumor control has been reported. Thus, in many models, CXCR6 + CD8 + T cells of resident phenotype participate in the control of primary tumor proliferation and metastasis ( 12 , 57 , 62 ). On the contrary, in NASH models with significant chronic inflammation, CXCR6 + P2X7 + T cells are able to destroy hepatocytes in a non-MHC-restricted manner which distinguishes them from classical CD8 + T RM ( 11 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An ambivalent role of CXCR6 + T cells in tumor control has been reported. Thus, in many models, CXCR6 + CD8 + T cells of resident phenotype participate in the control of primary tumor proliferation and metastasis ( 12 , 57 , 62 ). On the contrary, in NASH models with significant chronic inflammation, CXCR6 + P2X7 + T cells are able to destroy hepatocytes in a non-MHC-restricted manner which distinguishes them from classical CD8 + T RM ( 11 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cxcr6 - deficient mice or CXCL16 neutralizing Ab resulted in an enhanced metastasis to the liver by B16 melanoma cells or Lewis Lung tumor cells ( 61 ). In another preclinical model of lung metastases from breast cancer, it has been shown that CXCR6 - T effectors are the major subset preferentially egressing the tumor to form distant CXCR6 + T RM , whereas intratumoral CXCR6 + T cells are retained in the tumor ( 62 ). Breaking CXCR6-mediated retention in the tumor by anti-CXCL16 treatment resulted in more T cells egressing to the distant lung tissue and a decrease metastatic tumor burden ( 62 ).…”
Section: Role Of Cxcr6 + T Cells In Cancermentioning
confidence: 99%
“…Functionally, CXCR6 + Trm cells are required to sustain the proliferation and antitumor effects of cytotoxic T lymphocytes [42,50]. CXCR6 + Trms control tumor growth and metastasis [42,50,51] and are equipped with immunosurveillance to restrain tumor recurrence [52,53]. A recent study demonstrated that Klf5 loss led to a reduced number of myeloid-derived cells, particularly granulocytic myeloid-derived suppressor cells (gMDSCs), but an augmented number of both CD4 + and CD8 + T cells in pancreatic cancer models [26].…”
Section: Discussionmentioning
confidence: 99%
“…T-CELL. The T-CELL dataset was generated in our previous study [24]. The benchmark clustering labels of the T-CELL population were generated as a combination of protein-marker-based flow sorting labels and bioinformatics labels from Seurat v2.…”
Section: Experimental Datasetsmentioning
confidence: 99%